The Correlation between Knowledge Level and Self-Medication Behavior for the Common Cold among Students at the Roudhatul Quran Islamic Boarding School in Metro - Ida Nursanti; Mida Pratiwi; Diah Kartika Putri; Wina Safutri (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
The common cold is one of the most common illnesses experienced by boarding school students, caused by food or beverages consumed or the entry of microorganisms (bacteria, viruses, fungi) into the respiratory tract, leading to common cold symptoms. Many students engage in self-medication or self-treatment, particularly for the common cold, as it is considered mild and easily manageable without needing to visit a doctor. The purpose of this study is to determine the level of knowledge regarding self-medication for the common cold among students at the Roudlatul Quran Metro Islamic boarding school and to identify the relationship between the level of knowledge and self-medication behavior for the common cold. The research method used is a quantitative approach with a cross-sectional study design, involving a sample size of 222 respondents. The instrument used in this study is a questionnaire. Based on the research results, the level of knowledge among students at the Roudlatul Quran Metro Islamic boarding school was categorized as good (36.94%), adequate (61.71%), and poor (1.35%). Self-medication behavior was categorized as good (53.60%), adequate (42.79%), and poor (3.60%). This study concludes that there is a correlation between the level of knowledge and self-medication behavior for the common cold among students at the Roudlatul Quran Metro Islamic boarding school, with a P-value of 0.00.